PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. PRIMA BAJA BAHANA RAYA TANJUNG MORAWA - Purba, Ryan Fernando; Tinambunan, Anitha Paulina (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
This study aims to determine the effect of occupational health and safety on employee performance at CV. Prima Baja Bahana Raya Tanjung Morawa. The total population of  this study is 54 people. The analysis technique used in this study is multiple linear regression with equation K = 4.429 + 0.234 X1 + 0.627 X2 + e The results of the analysis show that occupational health and safety have a positive effect on the performance of employees of CV Prima Baja Bahana Raya Tanjung Morawa. From the results of the partial test, the t-test value for the health variable is more then 2.117  t table l 675 with a significance level of 0.039 less than equal 0.05 so that H0 is rejected and H1 is accepted. That is, health has a positive and significant effect on employee performance. The t-test value for the work safety variable is 4.934 more than t table 1.675 with a significance level of 0.000 less than equal 0.05 so that H0 is rejected and H1 is accepted. That is, work safety has a positive and significant effect on employee performance at CV Prima Baja Bahana Raya Tanjung Morawa.